Overcurrent Relay for Generation Distribution Utilization (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Distributed Generation (DG) is the production of electricity from a variety of renewable energy sources that is closer to the customer and load. The addition of distributed generation sources to the distribution networks alters the characteristics of distribution system and has an influence on its protection coordination. Relay protection plays a critical function in protecting a power system from various problems. Relay protection coordination reduces relay operating time and avoids relay failure. As a result, a fault analysis of the distribution network with and without distributed generation installation is required to determine the effects of installing DG at the radial system on overcurrent relay protection. The software programmed ETAP version 19.0 was used to represent an actual distribution system in this research paper. The consequences on the overcurrent protection relay were discovered as a result of the analysis. Simultaneously, the presence of an overcurrent relay following the installation of DG may no longer be dependable. As a result, it is critical to assess the effects of DG installation in order to verify that the protective zone can be properly protected.